PARTY AUTONOMY IN ADMINISTRATIVE (JUDICIAL) PROCEEDINGS - N. Bocharova (BRICS Law Journal, 2016)
In 2015 in Russian Federation the new Administrative Procedure Code was adopted. The Code uses the legal terms of action proceedings (administrative claim, administrative counterclaim, administrative plaintiff and defendant etc.) and determines “dispositive” rights of parties of administrative proceedings.The author’s intention is to analyze the scope of applying of the principle of party autonomy in administrative (judicial) proceedings. The article contains the comparative analysis of the principle in civil and administrative proceedings.